A novel design for storage of inner stress by colloidal processing on rock-like materials. (22nd March 2018) - Chen, Weichang; Wang, Sijing; Olatayo, Afolagboye Lekan; Fu, Huanran
Abstract: Inner stress exists in rocks, affecting rock engineering, yet has received very little attention and quantitative investigation because of uncertainty about its characteristics. Previous studies have suggested that the inner stresses of rock materials are closely related to their physical state variation. In this work, a novel mold was designed to simulate the storage process of inner stress in specimens composed of quartz sands and epoxy. Then, thermal tests were carried out to change the physical state of the specimens, and expansion of the specimens was monitored. The results indicated that inner stress could be partly locked by the mold and it could also be released by heating. It can be inferred from the analysis that one necessary condition of storage and release of inner stress is physical state variation. Additionally, by using an XRD method, the variations in the interplanar spacing of the quartz sands were detected, and the results reflect that inner stress could be locked-in aggregates (quartz sands) by a cement constraint (solid epoxy). The inner stress stored in quartz sands was calculated using height and interplanar spacing variations.